Effect of chloroquine on some clinical and biochemical parameters in non-response chronic hepatitis C virus infection patients: pilot clinical trial - Peymani, Payam; Ghavami, Saied; Yeganeh, Behzad; Tabrizi, Reza; Sabour, Siamak; Geramizadeh, Bita; Fattahi, Mohammad Reza; Ahmadi, Seyed Mehdi; Lankarani, Kamran B. (Acta Biomedica Atenei Parmensis, 2016)
Background: Hepatitis C virus infection frequently leads to chronic hepatitis C which may progress to cirrhosis and can be ended to hepatocellular carcinoma. This study aimed to investigate the effect of Anthropometric Parameters, Vit D3, Thyroid Function, Ferritin and Biochemistry Parameters in patients chronically infected with HCV with non-response criteria which was treated by chloroquine.Methods: This study was the continuation of our previous investigation with a triple-blind method in a randomized controlled pilot study. After understanding the study procedures, patients signed an informed consent form and were randomized into the treatment (chloroquine 150 mg once daily, for 8 weeks) and control (placebo once daily, for 8 weeks) groups. The inclusion criteria were male, between 18 and 60 years of age, confirmed chronic hepatitis C with non-response criteria, and Genotype 1.  Data were analyzed with an intention to treat perspective at the end follow up (12 weeks) considering to variables such as anthropometric parameters, Vit D3, thyroid function, ferritin and biochemistry parameters evaluated.Results: Although there were decreases in total weight (P-value=0.4), mid-arm circumference (P-value=0.05), and body mass index (P-value=0.04) there were increases in total body fat (P-value=0.8) and triceps skin fold thickness  (P-value=0.7) in the intervention group compared to the control group. Also, a reduction of AST (P-value=0.30), ALT (P-value=0.10), cholesterol (P-value=0.005), triglyceride (P-value=0.40) and ferritin (P-value=0.030) levels was seen in the intervention group during the follow up period. Our results also showed that serum TSH levels (P-value=0.5) were slightly higher in the chloroquine group than in the placebo group, though the trend was reversed for T3 (P-value=0.05) and T4 (P-value=0.04) levels. however, median of T3 and T4 were similar in both groups. A significant increase in vitamin D levels from 15 to 34 ng/ml was observed in the chloroquine group (P-value=0.04).Conclusions: The results suggest that chloroquine therapy may be very useful for HCV treatment in patients with non-response criteria, and helps to normalize some anthropometric parameters, biochemical, ferritin, and vitamin D status.